Female Presidents of the “Royal College of Pathologists”: Their Achievements and Contributions - Coupland, Sarah E.; Sandle, Lance N.; Osborn, Michael (Frontiers in Medicine, 2022)
The Royal College of Pathologists (RCPath) celebrates its Diamond Jubilee in 2022 since its opening by Her Majesty Queen Elizabeth II in 1962. One of the main remits of RCPath is the overseeing of the training of pathologists and scientists working in pathology’s 17 different specialties within the UK and across the globe. During its 60 years, three female Presidents have been elected: Dame Barbara Clayton (1984-1987), Dr Suzannah (Suzy) Lishman CBE (2014-2017) and Prof. Joanne (Jo) Martin (2017-2020). Whilst Clayton specialised in Chemical Pathology and its relevance to public health, both Lishman and Martin are diagnostic cellular histopathologists with differing areas of expertise. This article reviews the contributions of these three distinguished and inspirational female pathologists to Pathology (“the science behind the cure”), to healthcare, public health and education, medical research and to teaching. It highlights their qualities as leaders and mentors for those not only in medicine but in other career settings.